Early effects of Epac depend on the fine-tuning of the sarcoplasmic reticulum Ca2 + handling in cardiomyocytes. (January 2018) - Lezcano, N.; Mariángelo, J.I.E.; Vittone, L.; Wehrens, X.H.T.; Said, M.; Mundiña-Weilenmann, C.
Abstract: In cardiac muscle, signaling through cAMP governs many fundamental cellular functions, including contractility, relaxation and automatism. cAMP cascade leads to the activation of the classic protein kinase A but also to the stimulation of the recently discovered exchange protein directly activated by cAMP (Epac). The role of Epac in the regulation of intracellular Ca 2 + homeostasis and contractility in cardiac myocytes is still matter of debate. In this study we showed that the selective Epac activator, 8-(4-chloro-phenylthio)-2′- O -methyladenosine-3′, 5′-cyclic monophosphate (8-CPT), produced a positive inotropic effect when adult rat cardiac myocytes were stabilized at low [Ca 2 + ]o (0.5 mM), no changes at 1 mM [Ca 2 + ]o and a negative inotropic effect when [Ca 2 + ]o was increased to 1.8 mM. These effects were associated to parallel variations in sarcoplasmic reticulum (SR) Ca 2 + content. At all [Ca 2 + ]o studied, 8-CPT induced an increase in Ca 2 + spark frequency and enhanced CaMKII autophosphorylation and the CaMKII-dependent phosphorylation of SR proteins: phospholamban (PLN, at Thr17 site) and ryanodine receptor (RyR2, at Ser2814 site). We used transgenic mice lacking PLN CaMKII phosphorylation site (PLN-DM) and knock-in mice with an inactivated CaMKII site S2814 on RyR2 (RyR2-S2814A) to investigate the involvement of these processes in the effects of Epac stimulation. In PLN-DM mice, 8-CPT failed to induce the positive inotropic effect at low [Ca 2 + ]o and RyR2-S2814A mice showed no propensity to arrhythmic events when compared to wild type mice myocytes. We conclude that stimulation of Epac proteins could have either beneficial or deleterious effects depending on the steady-state Ca 2 + levels at which the myocyte is functioning, favoring the prevailing mechanism of SR Ca 2 + handling (uptake vs. leak) in the different situations. Graphical abstract: Highlights: Epac activation differentially modifies Ca 2 + handling and contractility depending on steady-state Ca 2 + levels in myocytes. Epac stimulation increases CaMKII autophosphorylation and CaMKII phosphorylation of PLN and RyR2 at different [Ca 2 + ]o . CaMKII-dependent PLN phosphorylation is crucial for determining the positive inotropic effect of Epac at low [Ca 2 + ]o . CaMKII-dependent RyR2 phosphorylation is responsible for the arrhythmogenic effects of Epac activation at high [Ca 2 + ]o . PKC is involved in the activation of CaMKII during Epac stimulation.